Simulation of low angle X-ray diffraction on multilayers subjected to diffusion - Fedorov, A.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Calculative method based on the Riccatti type differential equation was tested for simulation of low angle X-ray diffraction patterns from the one-dimensionally ordered multilayer. Some peculiarities of diffraction were revealed connected with asymmetrical distortion of the multilayer profile due to different processes on the layer boundaries.